"A whole new perspective on how the body fits together"—An evaluation of a cadaver laboratory experience for high school students. Issue 2 (1st November 2022) - Cale, Andrew S.; Byram, Jessica N.; Organ, Jason M.; Schmalz, Naomi A.
Abstract: The Center for Anatomy and Physiology Education has hosted interactive human cadaver laboratory tours for local high schools (ages 14–18) and undergraduate university students since 2014 to expose students to healthcare careers. Students receive information on the history of body donation and healthcare careers and observe human anatomy on prosections and with isolated organs. The goal of this study was to evaluate students' perceptions of the anatomy laboratory tours and their impact on students' interests in healthcare careers. Students completed pre‐ and post‐tour questionnaires. Responses were analyzed using thematic analysis and linguistic inquiry. Of the 261 students who completed pre‐tour questionnaires, 204 (78%) completed the post‐tour questionnaire. Before the tour, students anticipated learning about human anatomy and expected to only see but not touch a cadaver. Most students expressed excitement and/or nervousness. A few students viewed the laboratory tour as an opportunity to test if they could see themselves in a healthcare career. After the tour, most students indicated that the tour either met or exceeded their expectations. Students found the laboratory tour to be educational and interesting and were surprised by the opportunity to interact with the donor. Numerous students expressed an increased interest in healthcare careers after the tour. Overall, students perceived the tour as an engaging experience that improved their anatomical knowledge and reinforced/increased their interest in healthcare careers. Academic institutions can positively impact local students by implementing an anatomy tour, sharing access to their in‐house human cadaver laboratory, and recruiting instructors to share their anatomy expertise.